The application of connectors through a writing workshop system to improve english written expression in A2 level students. - Tejada Cedeño, Diego Benjamin; Soto Jimenez, Milena Paulette (Machala: Universidad Técnica de Machala, 2025)
Writing is a fundamental skill in language learning, yet it is often overlooked by both teachers and students during the teaching-learning process. When addressed, it tends to be taught using traditional methods without clear resources or structured practice. This study aimed to implement a writing workshop system incorporating conjunctive connectors to improve English written expression in A2-level learners at “Escola de Idiomas.” A mixed-method approach was applied with 12 A2-level students over four in-person sessions of 90 minutes each. The workshop provided an interactive, process-oriented environment focusing on using connectors, coherence, vocabulary development, grammar reinforcement, writing models, feedback, peer and self-revision, and metacognitive reflection. Data collection included pre- and post-tests with an analytical rubric assessing linguistic, pragmatic, stylistic, cognitive, and communicative dimensions. Additionally, an observation guide recorded participation, use of connectors, vocabulary, and revision practices. Results indicated significant improvement across all dimensions, showing better use of cohesive devices and enhanced text organization. Students actively engaged in the writing process, received feedback, and developed greater autonomy. The findings highlight the effectiveness of writing workshops as pedagogical tools to improve written expression in A2-level learners and promote deeper learning and effective writing habits. Future applications should consider extending workshop duration and incorporating ongoing writing opportunities to reinforce long-term writing development. Overall, this study demonstrates that structured writing workshops can provide valuable support for learners developing English writing skills, emphasizing the importance of guided practice and active student participation in language learning.
La escritura es una habilidad fundamental en el aprendizaje de idiomas, pero a menudo es pasada por alto tanto por los docentes como por los estudiantes durante el proceso de enseñanza-aprendizaje. Cuando se aborda, suele enseñarse utilizando métodos tradicionales, sin recursos claros ni práctica estructurada. Este estudio tuvo como objetivo implementar un sistema de talleres de escritura que incorporara conectores conjuntivos para mejorar la expresión escrita en inglés en estudiantes de nivel A2 de la “Escola de Idiomas”. Se aplicó un enfoque mixto con 12 estudiantes de nivel A2 durante cuatro sesiones presenciales de 90 minutos cada una. El taller proporcionó un entorno interactivo y orientado al proceso, centrándose en el uso de conectores, coherencia, desarrollo de vocabulario, refuerzo gramatical, modelos de escritura, retroalimentación, revisión entre pares y autoevaluación, así como reflexión metacognitiva. La recolección de datos incluyó pruebas diagnósticas y finales con una rúbrica analítica que evaluó las dimensiones lingüística, pragmática, estilística, cognitiva y comunicativa. Además, una guía de observación registró la participación, el uso de conectores, el vocabulario y las prácticas de revisión. Los resultados indicaron una mejora significativa en todas las dimensiones, mostrando un mejor empleo de los conectores cohesivos y una mayor organización textual. Los estudiantes participaron activamente en el proceso de escritura, recibieron retroalimentación y desarrollaron una mayor autonomía. Los hallazgos destacan la efectividad de los talleres de escritura como herramientas pedagógicas para mejorar la expresión escrita en estudiantes de nivel A2 y promover un aprendizaje más profundo y hábitos de escritura efectivos. Las aplicaciones futuras deberían considerar extender la duración de los talleres e incorporar oportunidades continuas de escritura para reforzar el desarrollo a largo plazo. En general, este estudio demuestra que los talleres de escritura estructurados pueden brindar un apoyo valioso a los estudiantes en el desarrollo de habilidades de escritura en inglés, enfatizando la importancia de la práctica guiada y la participación activa de los estudiantes en el aprendizaje de idiomas.
Keywords: CONNECTORS; WRITING WORKSHOP; WRITTEN EXPRESSION; LANGUAGE LEARNING; A2-LEVEL